111k views
5 votes
PLEASE HELP ME ASAP FOR 9 AND 10

PLEASE HELP ME ASAP FOR 9 AND 10-example-1
User Bismillah
by
6.4k points

1 Answer

5 votes

Answer:

9)

x^2 + 2x + 1 = (x + 1)^2

10)

x^2 - 6x + 9 = (x - 3)^2

Explanation:

To complete the square, add the square of half of the x-term coefficient.

Then use the factoring of a perfect square trinomial.

a^2 + 2ab + b^2 = (a + b)^2

a^2 - 2ab + b^2 = (a - b)^2

9)

x^2 + 2x + 1 = (x + 1)^2

10)

x^2 - 6x + 9 = (x - 3)^2

User AdamDynamic
by
6.5k points